Teaching Al-Quran among the Army Personels to increase the Level of Discipline - Zahimi Zainol Abidin; Noor Azmi Mohd Zainol; Daud Mohamed Salleh; Noor Afiza Razali (Perhimpunan Intelektual Muslim Indonesia, 2022)
Discipline has been characterised by several scholars as mental and moral activities that ensure conformity to rules and regulations for the development of society. In any organisation, the core problem that needs to be tackled is the disciplinary problem. Islam has promoted discipline as the interjecting factor which leads to success in this world and hereafter. This descriptive study will be discussing on the disciplinary problems among the army personnel, the contributing factors to the problem as well as coming up with Islamic approach solutions to the problem. Discipline and the military are synonymous and the ability to adhere to the rules that have been determined is the decisive factor which can lead to one's career excellence in the military. Zina, gambling, alcoholism is some of the criminal cases that have been committed by these personnel. It is believed that the occurrences of these cases are due to their lack of religious knowledge and practices (not performing prayers and being ignorant towards the Al-Quran), lack of parental guidance and family problems. This paper will investigate how the principles of Al-Quran can assist in the instillation of discipline as outlined in Islamic teachings among the military personnel. This study will use a qualitative method by reviewing related documents, interviews and carrying out observations. In order to establish high discipline levels within the Malaysian Armed Forces, a more in-depth assessment of the existing disciplinary problems, their contributing elements, and resolving actions based on the principles of the Al-Quran will be conducted.